2013
DOI: 10.1088/0960-1317/23/4/045009
|View full text |Cite
|
Sign up to set email alerts
|

Estimating residual stress, curvature and boundary compliance of doubly clamped MEMS from their vibration response

Abstract: Structural parameters of doubly clamped microfabricated beams such as initial curvature, boundary compliance, thickness and mean residual stress are often critical to the performance of microelectromechanical systems (MEMS) and need to be estimated as a part of quality control of the microfabrication process. However, these parameters couple and influence many metrics of device response and thus are very difficult to disentangle and estimate using conventional methods such as the M-test, static mechanical test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Since the in-plane Young's modulus of the nickel beams shows a small a small variation (0.5%) across the wafer as stated before, we assume the Young's modulus is constant, and the error of the extracted residual stress due to the uncertainty of the Young's modulus is analyzed in Section V-B. stress are compared to the results obtained using a resonance frequency method reported in [32]. For 26 nickel beams which have the same structure and were fabricated with the same process as the beams studied in this paper, the extracted values of residual stress also follow a nearly normal distribution with a mean value of 1.6 MPa with a standard deviation of 5.1 MPa, which closely agree with our results.…”
Section: Results Of Extracted Residual Stressesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the in-plane Young's modulus of the nickel beams shows a small a small variation (0.5%) across the wafer as stated before, we assume the Young's modulus is constant, and the error of the extracted residual stress due to the uncertainty of the Young's modulus is analyzed in Section V-B. stress are compared to the results obtained using a resonance frequency method reported in [32]. For 26 nickel beams which have the same structure and were fabricated with the same process as the beams studied in this paper, the extracted values of residual stress also follow a nearly normal distribution with a mean value of 1.6 MPa with a standard deviation of 5.1 MPa, which closely agree with our results.…”
Section: Results Of Extracted Residual Stressesmentioning
confidence: 99%
“…In addition, the initial beam curvature is not included in the beam model which degenerated the accuracy of the results. The last category involves dynamic tests, in which the test structures are powered into vibration, and the fundamental resonant frequency [29], [30] or multiple eigenmodes [31], [32] are measured to determine the residual stress. However, in [29]- [31], the effects of anchor compliance and non-flat initial profiles of test structures are neglected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth method uses the stress–frequency conversion. The natural frequency of a doubly clamped beam changes with the axial stress in the beam and can be measured using a scanning laser Doppler vibrometer system or frequency sweeping instruments, and then the stress can be determined [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely reported that MEMS bridges normally experience high stresses after fabrication process due to several factors including exposure to variable fabrication temperatures[73],[78]-[81].This causes the MEMS bridges to warp or buckle hence reducing the achievable downstate capacitance.…”
mentioning
confidence: 99%